Ahiṃsā: An analytical study on the basis of commentaries of Yoga Sūtra - Bandita Satapathy (Wolters Kluwer Medknow Publications, 2016)
Background: Ahiṃsā is a word formed by adding the negative prefix"a" to the word hiṃsā, a derivative from the root"hiṃs" meaning"to harm" and"to injure." Accordingly, Ahiṃsā carries the meaning of nonkilling. The most evolved concept of Ahiṃsā can be traced out in the Pātañjala Yoga Sūtras. Aim: The aim of the paper is to make a comparative study of multiple commentaries on Patañjali's Yoga Sūtra and to bring out the import of the concept of Ahiṃsā. Method: The concept of Ahiṃsā has been studied through the identification of commentaries. As well, a comparative and analytical study has been done using primary sources. Results: The study of various commentaries leads to the conclusion that most of the commentators have a common observation regarding the nature of Ahiṃsā, essentially necessary for yoga seekers. Conclusion: The comparative studies of commentaries of Pātañjala Yoga Sūtra bring out the essence of Ahiṃsā most objectively.